Engagement with the Community and Partnerships for Sustainable Food Production and Consumption in Portuguese Higher Education Institutions - Soares, Aldina (2022)
Trabalho apresentado em International Conference on Water, Energy, Food and Sustainability (ICoWEFS 2022), 10-12 de maio de 2022, Portalegre, Portugal